En modell för utveckling av nyckeltal i syfte att mäta processers prestanda : En fallstudie utförd hos LKAB Minerals AB - Linde, Viktor (2016)
When an organization is process-oriented, it is important that it can accurately measure process performance so as to be able to work with continuous improvements. Past studies on process- oriented work generally agree that measurement should be carried out; the problem is to determine what to measure. It has been said that what gets measured gets done. However, it seems that this is not always an accurate characterization. Most important is to measuring the "right things" in the "right way" to have any benefit from what gets measured. What are the "right things" depends on an organization's working conditions as this factor dictates the manner in which any measurement is performed.The purpose of this study was to investigate how an organization can measure process performance. To analyze this topic a case study was carried out at LKAB Minerals AB (LMAB) in Luleå. The case study was to empirically examine how key indicators can be developed to measure process performance. A theoretical model of the organization's sales process was built and tested. The reason why the sales process was selected was that top management determined that sales was strategically the most important activity if established LMAB objectives were to be achieved. The study is therefore limited to LKAB Minerals AB and examines only the indicators that measure sales performance.This study generated several interesting outcomes. Three key indicators that measure the sales performance process and several recommendations on how to develop process-oriented sales work were developed. The main finding of this study is the model that was developed to identify key performance indicators (KPIs). The model successfully identified quantifiable LMAB KPIs. The model is general and likely can be applied to other organizations. The model is based on scientific articles reviewed for this case study and summarizes findings from a wide range of scientific fields. Because the model is general and applicable to other organizations it may also be of interest to ...